2005
DOI: 10.1159/000086116
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelial Detachments with Retinal Vascular Anomalous Complex in Age-Related Macular Degeneration

Abstract: Purpose: To analyze and compare the angiographic features of retinal vascular anomalous complex (RVAC) in patients with a vascularized pigment epithelial detachment (PED) secondary to age-related macular degeneration. Methods: Retrospective evaluation of fluorescein and indocyanine green angiographies of 180 patients with occult choroidal neovascularization and PED. Results: On indocyanine green angiography (ICGA), RVAC demonstrated as a focal hyperfluorescence in connection with retinal choroidal anastomosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…There is considerable interest in developing ''disease in a dish'' models of human RPE. 7,8,[89][90][91] Successful maintenance of epithelial polarity and function in vitro has been a long sought goal for studying RPE-related diseases. 32,[92][93][94] In this study, we showed that ahRPE cells isolated and cultured from nhRPE 43 have functional and morphologic characteristics resembling native tissue.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable interest in developing ''disease in a dish'' models of human RPE. 7,8,[89][90][91] Successful maintenance of epithelial polarity and function in vitro has been a long sought goal for studying RPE-related diseases. 32,[92][93][94] In this study, we showed that ahRPE cells isolated and cultured from nhRPE 43 have functional and morphologic characteristics resembling native tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there has been an increased interest in RPE function and its role in multiple retinal diseases. [51][52][53][54][55][56] A corollary of this increased interest is the need to develop in vitro cell culture models to study a wide range of RPE physiology and pathophysiology. As in other organ systems, it has been difficult to create RPE cell lines and primary cultures with the appropriate morphologic and structural characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Zum einen kçnnen serçse PED mit meist randständiger okkulter CNV assoziiert sein und zum anderen kçnnen sie aber auch Folge einer retinalen angiomatçsen Proliferation (RAP) sein. [35,41]. Bei einer RAP ist klinisch und angiografisch meist im Zentrum der PED lokalisierte Gefäßproliferation erkennbar.…”
unclassified